Performance evaluation of the BH1750FVI sensor (low cost) in the measurement of global solar radiation (Research, Society and Development, 2021)
The aim of this work was to evaluate the performance of illuminance sensor BH1750FVI measuring the global solar radiation, using a microcontroller NodeMCU ESP8266; measurements from this sensor were compared and related to measurements from a reference meteorological station for comparison. For the estimation of solar global irradiance, the angular coefficient was 0.2201 and the residual was r = 0.726. For validation, values ​​of MBE, MBE%, RMSE and RMSE% were, respectively, -72.9 W/m², -23.86%, 164.3W/m² and 53.77%. For global (integrated) solar irradiation, the BH1750FVI sensor presented a coefficient of 0.22884 and residual r = 0.899; the validation values ​​MBE, MBE%, RMSE and RMSE% were, respectively -0.017 MJ/m², -0.13 %, 0.55 MJ/m² and 4.31%.